Combustion synthesis: An effective tool for preparing inorganic materials. (December 2018) - Liu, Guanghua; Chen, Kexin; Li, Jiangtao
Abstract: Combustion synthesis is a fast and energy-efficient process to prepare inorganic materials from self-sustained combustion reactions. It is widely used for preparing ceramics, metals, and their composites. The unique condition in combustion synthesis with high temperatures and large heating rates offers good opportunities to explore new materials and novel microstructures. This paper gives a viewpoint on recent progress in combustion synthesis, from fundamentals to applications. New results on theories, processings, and materials are reviewed, and perspectives on the development of combustion synthesis are provided.